INTERGENERATIONAL CONSUMER BEHAVIOR : A SYSTEMATIC REVIEW FROM 2001 UNTIL 2024 - Santoso, Ignatius Hari; I Made Sukresna (Jurnal Manajemen, 2025)
This systematic literature review explores the evolving landscape of intergenerational consumer behavior by analyzing 35 peer-reviewed articles, which were published between 2001 and 2024. Using the PRISMA framework, this review identifies the key pattern, mechanism, and cultural context that shape the consumers’ preference across generational cohort. The findings reveal a significant shift from the traditional unidirectional influence toward a bidirectional dynamic influence, where the younger generation increasingly influences the household consumption, specifically in digital and lifestyle related product category. This review uncovers six thematic clusters: Brand Identity and Emotional Meaning, Direction of Influence, Cultural Orientation, Lifestyle and Product Category, Advertising and Media Exposure, and Peer and Family Interaction.